2019
DOI: 10.1038/s41467-019-11831-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolated zero field sub-10 nm skyrmions in ultrathin Co films

Abstract: Due to their exceptional topological and dynamical properties magnetic skyrmions—localized stable spin structures—show great promise for spintronic applications. To become technologically competitive, isolated skyrmions with diameters below 10 nm stable at zero magnetic field and at room temperature are desired. Despite finding skyrmions in a wide spectrum of materials, the quest for a material with these envisioned properties is ongoing. Here we report zero field isolated skyrmions at T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 56 publications
12
90
0
Order By: Relevance
“…On an average, we notice an increase in barrier height of nearly 100 meV for skyrmions upon including the HOI. At low fields up to B − B c = 1.36 T, there is a transition from the normal radial collapse mechanism 22,34 without HOI to a chimera collapse mechanism 16,50 with HOI. Above B − B c = 1.36 T, the skyrmions merge into the FM background through the normal radial collapse without HOI, which remains unchanged after including HOI.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On an average, we notice an increase in barrier height of nearly 100 meV for skyrmions upon including the HOI. At low fields up to B − B c = 1.36 T, there is a transition from the normal radial collapse mechanism 22,34 without HOI to a chimera collapse mechanism 16,50 with HOI. Above B − B c = 1.36 T, the skyrmions merge into the FM background through the normal radial collapse without HOI, which remains unchanged after including HOI.…”
Section: Resultsmentioning
confidence: 97%
“…Due to the possibility of varying film composition and structure, these systems allow to modify magnetic interactions and thereby the properties of skyrmions. At such transition-metal interfaces, individual magnetic skyrmions with diameters ranging from a few 100 nanometers down to a few nanometers have been realized as a metastable state in the field-polarized ferromagnetic background 8,[10][11][12][13][14][15][16] as needed for applications.…”
mentioning
confidence: 99%
“…Based on first-principles calculations, it has been explained that the transition from a skyrmion lattice to isolated skyrmions is due to the modification of the exchange interactions rather than the Dzyaloshinskii-Moriya interaction 15,16 . Recently, it has been demonstrated that a similar frustration of exchange interactions along with the Dzyaloshinskii-Moriya interaction can induced zero-field skyrmions in Rh/Co bilay-ers on the Ir(111) surface 17 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Extensive research into skyrmions and their dynamics near room temperature (RT) in ferromagnets has greatly extended their use in spintronic devices because of their robust thermal stability and tunability. [ 19–25 ] However, the skyrmion Hall effect (SkHE), observed as a deflection with respect to the current direction, leads to the lateral accumulation and annihilation of skyrmions, [ 26 ] which greatly hinders ferromagnetic skyrmion‐based applications. These fundamental limitations are being addressed by investigating the behavior of skyrmions in ferrimagnets and antiferromagnets.…”
Section: Figurementioning
confidence: 99%